Influence of Surface Treatments on Erosion Behavior of Various Steel Alloys- A Literature Review - Sunil Kumar (Japanese Society of Tribologists, 2018)
This literature study is based on the research work conducted in the field of erosion behavior of steel alloys. The focus is on the surface modification of the steel alloys by heat treatment, surface hardening and surface coating methods. Laser cladding and laser hardening processes are also explained. The influence of tribological parameters on the erosion is explained. Steel alloys are chosen because of a wide number of applications due to their excellent properties. Efforts have been made to understand the cause and the remedial action towards the improvements in wear performance. Suitable surface treatment method on the steel alloys may definitely do this work but there should be a need of proper control over the process parameters. The environmental conditions of the laboratory are differing from the real working environment. Hence, the results which are satisfactory at the laboratory are not doing well in real place of application.